Doctor-Patient Communication and Preferred Terms Of Address: Respect and Kinship System (A Pragmatic Study) - Iragiliati, Emalia (Makara Human Behavior Studies in Asia, 2012)
The concept of face, face work and politeness model in the doctor-patient communication which is based on English for Academic Purposes: medical relied on the face as a social construct. This study investigates greeting in the form of second person pronoun based on the kinship system in terms of address to show respect as preferred by patients in Indonesia. There were twenty-six (26) male out-patients and forty (40) female patients. Data from the questionnaire consist of patients’ gender, age, education, marital status and preferred second person pronoun in terms of address. They were analyzed using the ‘interaction model’. The research showed on the importance of the use of greetings in the form of second person pronoun based on kinship system to show respect preferred as follows: Father/Bapak, Elder Brother/Mas, Younger Brother/Dik, Mother/Ibu, Elder Sister/Mbak, and Younger Sister/Adek. The married female patients prefer Mother/Ibu rather than Older Sister/Mbak and the married male patients prefer Father/Bapak rather than Older Brother/Mas. Thus, the patients’ choices on terms of address were based not only on age but marital status. These findings were different from the previous research as it was based on age to show respect.